1976
DOI: 10.3109/02844317609105204
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Incisional Hernias and Defects in the Anterior Abdominal Wall Using Dermal Grafts

Abstract: The technique and results of using autografts of dermis to repair defects in the anterior abdominal wall is shown. Dermal grafting was used in altogether 15 cases. 7 with extremely large incisional hernias, and 8 with defects after malignant abdominal wall tumours. The surgical method is described and the follow-up 1 to 4 years postoperatively has shown a very satisfactory result in 13 cases. In one case there was a postoperative haematoma with subsequent graft necrosis and in the other there was a residual he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Histological studies have shown that subcutaneous implantation of FTSG does not give rise to cyst formation or malignant change, and recent animal studies have shown excellent graft survival in the abdominal wall [ 16 , 17 ]. However, interest in this technique faded with the introduction of synthetic materials such as polypropylene and polyester, since when FTSG has only been used sporadically in selected cases [ 18 , 19 ]. Because of the increasing awareness of the problems related to the use of current synthetic materials, it is time to reassess alternative methods such as FTSG [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies have shown that subcutaneous implantation of FTSG does not give rise to cyst formation or malignant change, and recent animal studies have shown excellent graft survival in the abdominal wall [ 16 , 17 ]. However, interest in this technique faded with the introduction of synthetic materials such as polypropylene and polyester, since when FTSG has only been used sporadically in selected cases [ 18 , 19 ]. Because of the increasing awareness of the problems related to the use of current synthetic materials, it is time to reassess alternative methods such as FTSG [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of autologous skin as reinforcement in hernia repairs is an alternative method that may lead to lower recurrence and complication rates by avoiding the use of foreign material. Autologous skin graft has been used in hernia repair before, but to our knowledge only in the onlay position (11)(12)(13)(14). Before executing clinical trials on parastomal hernia repair with autologous skin in an intraperitoneal position, experiments on both tissue biology as well as mechanical studies must therefore be performed.…”
Section: Introductionmentioning
confidence: 99%
“…The use of autologous deepithelialized and nondeepithelialized skin for inguinal and ventral hernia repair has been described in the literature as an "auto-dermoplasty" for abdominal wall reconstruction. 31 Therefore, the concept of using biologic tissue for structural repair of abdominal wall defects is not necessarily a new concept. 32 Bioprosthetic mesh materials are defined as biologic tissue derived from a mammalian source, either allograft or xenograft.…”
Section: Evolution Of the Use Of Bioprosthetic Meshmentioning
confidence: 99%